Development and application of a novel peptide nucleic acid probe for the specific detection of helicobacter pylori in gastric biopsy specimens - Guimarães, N. (2007)
In this work, a fluorescence in situ hybridization (FISH) method for the rapid detection of Helicobacter pylori using a novel peptide nucleic acid (PNA) probe is reported. Laboratory testing with several different bacterial species, including other Helicobacter spp., has shown that this probe is highly specific for H. pylori strains. In addition, the PNA FISH method has been successfully adapted for detection of the pathogen in paraffinembedded gastric biopsy specimens.